Empowering Mosque Youth through Technological Innovation: Implementation of Web-Based Information Systems - Akbar Iskandar; Fathurrahman; Karan Sharma (Jurnal Abdimas Cendekiawan Indonesia, 2025)
This community service activity aims to design an information system and empower the Nurul Ihsan Mosque Youth Association in Makassar through the use of information technology. So far, the management of activities, finances, and membership data has been done manually, which often causes delays, irregularities, and difficulties in accessing information. So to answer these challenges, the implementation team designed and implemented a web-based information system using the waterfall method approach, which includes needs analysis, design, implementation, testing, and maintenance. This system facilitates administrators in managing data in a structured and real-time manner, as well as opening up access to information for members and the wider community in a transparent manner. As part of the impact evaluation, a satisfaction test was conducted on 30 respondents, consisting of administrators and members of the mosque youth. The results of the statistical analysis showed that 90% of respondents stated that they were very satisfied with the ease of use of the application, the speed of accessing information, and the intuitive interface. The average value of the overall satisfaction level reached the maximum scale, indicating positive acceptance and effectiveness of the system in supporting organizational activities. The implementation of this system not only improves the efficiency of the administrators' work but also strengthens member participation and builds a more professional and adaptive organizational image to technological developments. This initiative proves that appropriate digital innovation can be a key driver in strengthening the role of religious organizations in modern society.